Fabrication and Optimization of Febuxostat-loaded Liposomal Gel Using the Box–Behnken Design for Gout Treatment - Bhushan Rane; Punam Gadekar; Vaibhav Patil; Akash Amkar; Ashish Jain (Nano Biomedicine and Engineering)
Monosodium urate crystals form and deposit in and around the joints due to hyperuricemia, a condition characterized by a prolonged increase in serum urate levels. This leads to tissue supersaturation with urate and results in gout, a prevalent form of inflammatory arthritis. Gout can be effectively managed with febuxostat (FBT), a nonpurine selective xanthine oxidase inhibitor. Despite the efficacy of FBT, its use is limited by poor oral bioavailability and aqueous solubility, which are influenced by its co-administration with food and enzymatic degradation. To address the formulation challenges, topical liposomal formulations can be utilized. These formulations, which leverage the affinity of liposomes for keratin and their ability to penetrate deeper into the skin, offer improved drug absorption. This study aimed to develop a liposomal formulation with soy lecithin and cholesterol using the thin-film hydration method, optimized via the Box–Behnken design. The optimized liposomal formulation was then incorporated into a transdermal gel prepared with Carbopol 934 using the dispersion method. The optimized liposomal formulation demonstrated favorable properties, including a vesicle size of 392.5 ± 11.02 nm, zeta potential of 28 ± 6.13 mV, polydispersity index of 0.127, and high entrapment efficiency as confirmed via transmission electron microscopy. The resulting transdermal gel exhibited the necessary antibacterial activity; excellent stability; in vitro release of 81.33% ± 1.19% over 7 h; and appropriate pH, viscosity, spreadability, and gel strength. Overall, the liposomal gel formulation represents a highly effective approach for transdermal drug delivery.